2021
DOI: 10.3389/fmicb.2021.744834
|View full text |Cite
|
Sign up to set email alerts
|

Energy Availability Determines Strategy of Microbial Amino Acid Synthesis in Volatile Fatty Acid–Fed Anaerobic Methanogenic Chemostats

Abstract: In natural communities, microbes exchange a variety of metabolites (public goods) with each other, which drives the evolution of auxotroph and shapes interdependent patterns at community-level. However, factors that determine the strategy of public goods synthesis for a given community member still remains to be elucidated. In anaerobic methanogenic communities, energy availability of different community members is largely varied. We hypothesized that this uneven energy availability contributed to the heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Compared to Methanosarcina , bacterial genera in the community (e.g., SAOB) are at a disadvantage in the competition for acetate and therefore adopt a survival strategy that reduces their ability to synthesize AAs (especially high-cost AAs). In our previous study ( Yao et al, 2021 ), we found that SAOBs generally cannot synthesize the majority of the 20 AAs, especially those with medium and high synthetic costs. This increases the AA’s dependence of SAOBs and then reduces its metabolic activity.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Compared to Methanosarcina , bacterial genera in the community (e.g., SAOB) are at a disadvantage in the competition for acetate and therefore adopt a survival strategy that reduces their ability to synthesize AAs (especially high-cost AAs). In our previous study ( Yao et al, 2021 ), we found that SAOBs generally cannot synthesize the majority of the 20 AAs, especially those with medium and high synthetic costs. This increases the AA’s dependence of SAOBs and then reduces its metabolic activity.…”
Section: Discussionmentioning
confidence: 92%
“…We summarized the daily production of biogas and the proportions of gas components in each reactor during the stabilization phase after reactor recovery and tested the differences among reactors by Tukey’s test ( Figure 1 ). When acetate is used as the carbon source, methane is produced through two pathways, one is that acetate can be converted to methane directedly by acetoclastic methanogens, and the other is that acetate is oxidized by syntrophic acetate-oxidizing bacteria (SAOB) to produce hydrogen and carbon dioxide which are later converted to methane by hydrogenotrophic methanogens ( Schink, 1997 ; Yao et al, 2021 ). Thus, the biogas production as well as the biogas composition can reflect the activity of methanogens and bacteria in the microbial community.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations